Airline alliances, antitrust immunity and market foreclosure - Volodymyr Bilotkach; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper examines the issue of market foreclosure by airline partnerships with antitrust immunity. Overlapping the data on frequency of service and passenger volumes on nonstop routes on the transatlantic airline market with the information on dynamics of airline partnerships, we find evidence consistent with the airlines operating under antitrust immunity refusing to accept connecting passengers from the carriers outside of the partnership at respective hub airports. When an airline partnership is granted antitrust immunity, airlines outside this partnership end up reducing their traffic to the partner airlines' hub airports by 2.6-8.5 percent (depending on the specification and estimation technique involved). Our results suggest ambiguous welfare effects of antitrust immunity on some markets, where previous studies indicated airline consolidation should benefit consumers.
Keywords: L41; L93; K21; 330; air transportation; alliances; antitrust immunity; foreclosure; Luftverkehrsgesellschaft; Passagierluftfahrt; Strategische Allianz; Wettbewerbsbeschränkung; Wohlfahrtseffekt; USA; Europa